Depression and Suicide in Children and Adolescents: Prevention, Intervention, Postvention. - Patros, Philip G. (1989)
Keywords: dept.csp; faculty_collection; sabbatical_report

Self-efficacy in university faculty. - Landino, Rita A; Owen, Steven V (Journal of Vocational Behavior, 1988)
This study tested a causal model of academic self-efficacy in faculty at a large New England research university, focusing specifically on gender as one of 12 antecedent variables. Academic self-efficacy was defined as an estimate of confidence in one's ability to perform various tasks classified as research, service, and teaching in a university setting. The variables were drawn from Bandura's theory of self-efficacy and from characteristics of the university work setting. Data was obtained by mail response to a researcher-designed instrument: the Measure of Self-Efficacy in Academic Tasks (MSEAT). The findings show that being female contributed to feeling less efficacious about research tasks indirectly through the mediating influence of intervening variables. Feeling nourished and rewarded by a department and being male contributed to service self-efficacy. Teaching self-efficacy was not explained by the causal model. The implications of these findings are discussed in terms of campus socializing interventions, departmental research climate, and university incentives for female faculty. © 1988.
Keywords: dept.csp

Grief among healthcare workers: A comparative study - Lerea, L Eliezer; Limauro, Barbara F (The Journals of Gerontology, 1982)
This investigation examined the prevalence and nature of grief in response to patient suffering, loss, or death among healthcare workers employed at a general hospital and a skilled nursing facility. A questionnaire was constructed for this purpose. Approximately two-thirds of the skilled nursing facility personnel remembered experiencing bereavement as a reaction to the crises of their geriatric patients. Mourning occurred among virtually all of the general hospital personnel who usually serve younger patients. Healthcare personnel mourned most often for those persons who suffered or died of cancer. A selected sample of respondents recalled that psychological symptoms of grief were more evident than physical. Both symptom types often persisted for more than 1 month. Since grief is common among nurses and aides employed at the two medical settings, bereavement counseling is suggested for those healthcare personnel who require this service.
Keywords: United States; classification; dept.csp; geriatrics; grief; health care personnel; hospital; normal human; nursing home; psychological aspect; questionnaire; therapy